Corruption and Economic Growth: Evidence from Four ASEAN Countries, 2012–2022 - Onny Juliansyah; Yunastiti Purwaningsih; Suryanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Corruption remains a persistent institutional problem that potentially constrains economic performance, particularly in developing regions such as Southeast Asia. This study examines the effect of corruption on economic growth in four ASEAN countries—Indonesia, Laos, Myanmar, and Cambodia—during the period 2012–2022. Using panel data regression analysis, this research incorporates corruption perception, human development, and constitutional quality as key explanatory variables influencing economic growth, measured by real GDP per capita. The Fixed Effect Model (FEM) is employed based on the results of the Chow and Hausman tests, indicating its suitability for capturing country-specific characteristics. The empirical findings reveal that corruption exerts a negative but statistically insignificant effect on economic growth, suggesting that its impact operates indirectly through inefficiencies in resource allocation and production processes. Meanwhile, the Human Development Index demonstrates a positive and statistically significant effect on economic growth, highlighting the crucial role of human capital investment in fostering sustainable economic performance. Constitutional quality shows a positive but insignificant relationship with economic growth, implying that institutional improvements alone may not be sufficient without effective enforcement and governance mechanisms. Overall, the results emphasize that enhancing human development remains the most effective strategy for accelerating economic growth in countries with relatively high levels of perceived corruption. These findings provide important policy implications for ASEAN governments in prioritizing human capital development alongside institutional reforms to achieve long-term economic growth.